Secukinumab in refractory non-infectious anterior uveitis - Olivas-Vergara, Otto M.; Hernanz, Inés; Borges-Deniz, Pablo E.; Romero-Bueno, Fredeswinda; Sanchez-Pernaute, Olga; Carreño, Ester (Frontiers in Ophthalmology, 2025)
BackgroundSecukinumab is a monoclonal antibody that selectively neutralizes interleukin-17A and has shown efficacy in the treatment of psoriatic arthritis, psoriasis, and axial spondyloarthritis. Its use in non-anterior non-infectious uveitis is controversial, with evidence generally not supporting its effectiveness in these conditions. However, the role of secukinumab in anterior non-infectious uveitis remains unclear.MethodsCase series. Five patients with biological therapy-refractory non-infectious anterior uveitis who were treated with secukinumab were included.ResultsAll 5 patients experienced a uveitis flare-up during treatment, and secukinumab failed to induce long-term remission in 2 of these patients, who also had uncontrolled systemic disease.ConclusionSecukinumab failed to prevent uveitis flare-up in these patients with biological therapy-refractory disease. Further studies are necessary to determine the potential role of secukinumab in the treatment of anterior uveitis.